2022
DOI: 10.3390/ijms23063389
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles: Interplay with the Extracellular Matrix and Modulated Cell Responses

Abstract: The discovery that cells secrete extracellular vesicles (EVs), which carry a variety of regulatory proteins, nucleic acids, and lipids, has shed light on the sophisticated manner by which cells can communicate and accordingly function. The bioactivity of EVs is not only defined by their internal content, but also through their surface associated molecules, and the linked downstream signaling effects they elicit in target cells. The extracellular matrix (ECM) contains signaling and structural molecules that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…Interestingly, some of these ECM-vesicles seem to confer immunomodulatory effects on immune cells [35]. For instance, the application of matrix-bound vesicles on macrophages induces the expression of anti-inflammatory markers such as Fizz-1 and interleukin (IL)-4 indicating a polarization towards an M2 phenotype [30,35]. Accordingly, our results show that L-HG-derived vesicles also participate in tissue regeneration and repair based on a wound healing alveolar epithelial model.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Interestingly, some of these ECM-vesicles seem to confer immunomodulatory effects on immune cells [35]. For instance, the application of matrix-bound vesicles on macrophages induces the expression of anti-inflammatory markers such as Fizz-1 and interleukin (IL)-4 indicating a polarization towards an M2 phenotype [30,35]. Accordingly, our results show that L-HG-derived vesicles also participate in tissue regeneration and repair based on a wound healing alveolar epithelial model.…”
Section: Discussionmentioning
confidence: 63%
“…MSCs-derived EVs are generated and released into the extracellular environment to maintain tissue homeostasis. They are commonly characterized by a lipid membrane bilayer sharing some surface features [30]. However, their content, biogenesis, and release could depend on the surrounding environment [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key finding of our study is that non-NE cells synthesize and secrete a large amount of ECM that is carried primarily by EVs. ECM and adhesion receptors such as integrins are frequent cargoes of SEVs in both normal and cancer cell types and have been previously implicated in driving cancer aggressiveness and metastasis 27,[65][66][67] . Interestingly, we found that both epithelial (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Tracks are vesicles along collagen fibers. Some EVs, known to be involved in cell-cell communication, were already described as attached to the ECM 41 . Because tracks contain cell membrane, we then analyzed and characterized their ultrastructure using different and complementary microscopy approaches.…”
Section: Tracks Are Linked To Cell Adhesion Strength With Collagen Fi...mentioning
confidence: 99%